Pain, Sedation, and Delirium Management in the Neurocritically Ill: Lessons Learned from Recent Research - Gélinas, Céline; Klein, Kate; Naidech, Andrew M.; Skrobik, Yoanna (Seminars in Respiratory and Critical Care Medicine, 2013)
Critically ill patients with a primary neurological injury or illness pose unique challenges for pain, agitation, and delirium management in intensive care units (ICUs). Detection and monitoring can be limited by contextual level of consciousness (LOC) alterations, cognition, expression, or language deficits. Recent data suggest that existing pain assessment tools may not be applicable to all neurocritically ill patients, especially in those with LOC alterations and atypical pain-associated behaviors. Targeted sedation goals may be neurologically disease specific; for instance, intracranial pressure (ICP) targets will supersede sedation titration by other criteria. Technology such as bispectral index (BIS) may be beneficial in avoiding excessive medication administration in deeply sedated neurologically injured ICU patients. Given the wide variety of pathology in the neurocritically ill patients, it is unclear if delirium can be diagnosed and unequivocally differentiated from symptoms of the underlying neurological pathology. However, delirium symptoms may herald life-threatening primary insult progression or result from a new secondary neurological injury and should be monitored. Patients with neurological injury or illness are often excluded from ICU studies addressing pain, sedation, and delirium, but this need not be the case. We review what is understood in this area based on current evidence.
Keywords: pain; sedation; delirium; neuro; intensive care unit